2022
DOI: 10.1590/0037-8682-0555-2021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Cryptosporidium spp. obtained from fecal samples of immunosuppressed patients from Brazil

Abstract: Background: Cryptosporidium spp. are pathogenic protozoans that play an important role in developing diseases in the elderly, children, and immunosuppressed individuals. Methods: The objective of this study was to detect and genetically characterize Cryptosporidium spp. in kidney transplanted patients (n = 97 samples; group 1) and immunosuppressed individuals from an outpatient clinic suspected of having Cryptospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…It is important to point out that the publications may have failed to report the IbA10G2 subtype because they were not related to cryptosporidiosis outbreak studies. Although there are few studies from South America, the IbA10G2 subtype was the most frequently reported 29 . The C. hominis subtype family with the highest number of descriptions was subtype Ia, followed by Ib and Ie.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that the publications may have failed to report the IbA10G2 subtype because they were not related to cryptosporidiosis outbreak studies. Although there are few studies from South America, the IbA10G2 subtype was the most frequently reported 29 . The C. hominis subtype family with the highest number of descriptions was subtype Ia, followed by Ib and Ie.…”
Section: Discussionmentioning
confidence: 99%